USING A CASE METHOD TO BUILD ENVIRONMENTAL COMPETENCE OF STUDENTS OF ECONOMICS IN ESP LESSONS - Nataliia Ishchuk (Іноземна філологія)
Today’s global socio-economic factors determine the strategy of education development. The problem of high-quality training in the fi eld of economics specialists is gaining relevance, as it provides a new impetus for the modernization of the economy, integration, social mobility, and development of the labor institute on new principles of maintaining competitiveness. To prepare specialists who can be effective in the modern labor market, teachers in higher education institutions need to use modern methods which help connect academic learning with real-life practice. The purpose of the article is to theoretically define the eff ectiveness of the case method in practical foreign language classes, which directly aims at the formation of professional foreign language environmental competence of economics students of higher education institutions. Theoretical (critical analysis, synthesis, modeling), empirical (observation, generalization, classification, description), and experimental research methods have been used in our work. The case method is the independent activity of students in a simulated situation which provides an opportunity to combine theoretical training and practical skills. All cases are divided into simple cases, case-exercises, case-examples, case-solutions, and complex cases. The classic version of the case method is characterized by preparatory, main, and fi nal stages. Each case has an educational function and requires a certain amount of time. The case method creates opportunities to creatively use lexical material and allows students to adapt to real and potentially possible situations. It serves to analyze and systematize information, teaches critical thinking and objective assessment, and develops logic and flexibility in thinking. With the help of this method, students have the opportunity to show initiative and feel independent in mastering theoretical concepts and practical skills. The case method, as an interactive method, has a positive eff ect on the motivation of economics students. Its use in foreign language classes for the formation of environmental students’ competence is necessary and eff ective because the process of acquiring environmental knowledge must become continuous and should correspond to the conditions of modern human development..